FILOSOFI CANGGET AGUNG DALAM TRADISI MASYARAKAT LAMPUNG - Cathrin, Shely (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This study aims to find the philosophical valuescontained in the Cangget tradition in Lampung Pepadun Society. An understanding of these philosophical values is very important to maintain the existence of the Cangget tradition in the midst of globalization. To achieve this goal, the researcher conducted a literature review of several studies on Cangget and conducted interviews with several traditional leaders of Lampung Pepadun. The object of the research material is the Cangget tradition in the culture of the people of Lampung Pepadun which is analyzed from the formal object of the philosophy of culture. The results of the study indicate that the Cangget tradition is included in one of Lampung's cultures in the form of community social activities. This tradition has several meanings, among others, as a form of traditional celebration of the Lampung people, as well as a form of the efforts of the people of Lampung Pepadun to maintain the purity of the traditions and customs of the people. The Cangget tradition also has philosophical values, including the value of togetherness or social value, the value of unity, the value of honor, the value of democracy, and the economic value.